A Preliminary Evaluation Of USIM Students’ Car Booking - Muhammad, N.M.Z.; Nurdiana, A. (Usim Press, 2024)
Minggu Penyelidikan Dan Inovasi Sains Dan Teknologi 2022 (MPIST 2022): “Synergizing Innovation And Research Through Science And Technology”/ Editor : Hanis Nadia Yahya, Norhidayah Azman, Shahrina Ismail, Farah Hamizah Puad, Umul Ain’syah Sha’ari, Mohd Fauzi Haris 7th December 2022 I Organized by: Fakulti Sains dan Teknologi